2003
DOI: 10.1161/01.cir.0000092888.63239.54
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Angiotensin-(1-7) in Ischemic Cardiomyopathy

Abstract: Background-Accumulating evidence suggests that angiotensin-(1-7) (Ang- [1][2][3][4][5][6][7]) may play an important role in counteracting the pressor, proliferative, and profibrotic actions of angiotensin II in the heart. Thus, we evaluated whether Ang-(1-7) is expressed in the myocardium of normal rats and those in which myocardial infarction was produced 4 weeks beforehand. Methods and Results-The left coronary artery in 10-week-old Lewis rats was either ligated (nϭ5) or exposed but not occluded in age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 32 publications
7
113
1
Order By: Relevance
“…25 In addition to an intracellular localization within the kidney, 25,26 Ang II has been shown to be in tubular fluid, 27 interstitial fluid compartments, and urine, 1,28 making it available as a substrate for either intracellular or tubular formation of Ang-(1-7). Because ACE2 has been shown to be present in the urine in addition to the tubular location described in these studies (unpublished data from Dr Mark Chappell, 2003), it is likely that it also can be secreted. Thus both renal intracellular and interstitial formation of Ang-(1-7) may occur.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…25 In addition to an intracellular localization within the kidney, 25,26 Ang II has been shown to be in tubular fluid, 27 interstitial fluid compartments, and urine, 1,28 making it available as a substrate for either intracellular or tubular formation of Ang-(1-7). Because ACE2 has been shown to be present in the urine in addition to the tubular location described in these studies (unpublished data from Dr Mark Chappell, 2003), it is likely that it also can be secreted. Thus both renal intracellular and interstitial formation of Ang-(1-7) may occur.…”
Section: Discussionmentioning
confidence: 71%
“…The specificity of the Ang-(1-7) antibody for ICC has been previously described. 16,17 Briefly, it does not cross-react with Ang I or Ang II. The peptide sequence used to make the ACE2 antibody is unique to ACE2 but not ACE or the ACE2 homologue collectrin 18 ; in Western blotting, the antibody recognizes only two bands in the renal cortex at 89 and 125 kDa that correlate with the nonglycosylated and glycosylated forms of ACE2.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…In this regard, there is pharmacological evidence for the presence of a selective Ang-(1-7) receptor in the heart (Ferreira et al, 2001) and coronary arteries (Porsti et al, 1994). In addition, immunoreactivity for Ang-(1-7) was recently detected in cardiac myocites (Averill et al, 2003). Indeed, the recently characterized Ang-(1-7) receptor, Mas , is expressed in the rodent heart (Metzger et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The heart was our first target in assessing the interactions of ACE2 and Ang-(1-7), because myocytes expressed the components of the system, 43 the ACE2 gene is abundant in the rat heart (Figure 1), and the heptapeptide reversed arrhythmia reperfusion injury. 44 In addition, Loot et al 45 found that chronic infusion of Ang-(1-7) restored cardiac contractility after myocardial infarction (MI).…”
Section: Ace2 and Ang-(1-7)mentioning
confidence: 99%
“…44 In addition, Loot et al 45 found that chronic infusion of Ang-(1-7) restored cardiac contractility after myocardial infarction (MI). Knowledge that the density of Ang-(1-7) immunostaining increased in the penumbra region surrounding the rat ischemic myocardium 43 led us first to evaluate the expression of ACE2 28-days after MI in rats with an associated blockade of AT 1 receptors. 46 A 3-fold increase in ACE2 mRNA within the viable myocardium was found in these experiments, correlating with increases in plasma concentrations of Ang-(1-7).…”
Section: Ace2 and Ang-(1-7)mentioning
confidence: 99%